Perlindungan Hak Kekayaan Intelektual (HaKI) Ditinjau Dari Epistimologi - Nizwana, Yulia; Rahdiansyah, Rahdiansyah (UIR Law Review, 2019)
Along with the times, the protection of the rights possessed by every human being needs to be regulated, including the case with Intellectual Property Rights (IPR). As one of the countries that is very diverse and has a lot of potential in the field of IPR, Indonesia has also long been actively involved in both regional and international frameworks in the field of IPR. Philosophy of science is really worth studying by anyone. Philosophy of science has a role in human life. Philosophy of science is knowledge that seeks truth. Branches of philosophy include Ontology, Epistemology, and Axiology. Then IPR protection will be assessed in terms of epistemology and axiology. The formulation of the problem discussed is why IPRs need to be protected, how IPR Protection is evaluated from Epistemology,. The approach method used is Normative Juridical, discussion of issues relating to the Protection of Intellectual Property Rights in terms of Epistemology. The results of the discussion, the reason why Intellectual Property Rights Need to be Protected is because IPR is natural rights, Reputation Protection, Encouragement and rewards from innovation and creation, Then supported by 5 basic theories of IPR protection: Reward Theory, Recovery Theory, Incentive Theory, Risk Theory, Economic Growth Stimulus Theory. Protection of Intellectual Property Rights in terms of Epistemology. Epistemology discusses three things, namely the object of philosophy (ie thought), how to obtain philosophical knowledge and measure of truth (philosophical knowledge) how humans seek philosophical knowledge. For example why IPR needs to be protected, the most profound and fundamental answer is IPR protection is a protection against the intellectual idea of ​​someone who was born naturally the gift of the God, that is from God where every human being was created with advantages including the advantages of intellectual ideas that are certainly different every human beings, so that intellectual ideas need to be protected because they are subjective and natural.